2015
DOI: 10.5194/angeo-33-185-2015
|View full text |Cite
|
Sign up to set email alerts
|

Tidal signatures of the thermospheric mass density and zonal wind at midlatitude: CHAMP and GRACE observations

Abstract: Abstract. By using the accelerometer measurements from CHAMP and GRACE satellites, the tidal signatures of the thermospheric mass density and zonal wind at midlatitudes have been analyzed in this study. The results show that the mass density and zonal wind at southern midlatitudes are dominated by a longitudinal wave-1 pattern. The most prominent tidal components in mass density and zonal wind are the diurnal tides D0 and DW2 and the semidiurnal tides SW1 and SW3. This is consistent with the tidal signatures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 47 publications
(73 reference statements)
5
23
0
Order By: Relevance
“…This corresponds to a wave speed of about 590 m/s. The propagation speed is consistent with previous model and observational work reporting a phase speed of the equatorward wind surge of about 600 m/s [e.g., Fuller‐Rowell et al , ; Fujiwara et al , ; Ritter et al , ; Xiong et al , ]. The peak vertical disturbed wind is about 40–50 m/s around −0:20, which is weaker in comparison to those in the horizontal directions.…”
Section: Resultssupporting
confidence: 90%
“…This corresponds to a wave speed of about 590 m/s. The propagation speed is consistent with previous model and observational work reporting a phase speed of the equatorward wind surge of about 600 m/s [e.g., Fuller‐Rowell et al , ; Fujiwara et al , ; Ritter et al , ; Xiong et al , ]. The peak vertical disturbed wind is about 40–50 m/s around −0:20, which is weaker in comparison to those in the horizontal directions.…”
Section: Resultssupporting
confidence: 90%
“…Similar WN1 patterns in thermospheric mass density and zonal wind are also found at the southern middle latitudes, and the most prominent tidal components are D0 and DW2 (e.g. Xiong et al, 2015b). One interesting feature of D0 is that it shows an anti-phase diurnal variation between hemispheres both in the F region electron density as well as in the thermospheric mass density and zonal wind (Xiong et al, 2015b).…”
Section: Nonmigrating Tides At Middle Latitudessupporting
confidence: 55%
“…Xiong et al, 2015b). One interesting feature of D0 is that it shows an anti-phase diurnal variation between hemispheres both in the F region electron density as well as in the thermospheric mass density and zonal wind (Xiong et al, 2015b). By employing the global ionosphere-thermosphere model (GITM) simulation, H. found that the thermospheric zonal wind plays an important role in causing the WN1/WN2 patterns of the F region electron density at middle latitudes, but additional contributions are needed to explain the full extension of observed tides.…”
Section: Nonmigrating Tides At Middle Latitudesmentioning
confidence: 99%
“…Xiong et al . [] show CHAMP and Gravity Recovery and Climate Experiment (GRACE) observations of mass density that present a wave 1 pattern in longitude (more clearly in the southern hemisphere than the northern hemisphere) that resembles the WINDII O( 1 D) VER and temperature variations with longitude.…”
Section: Discussionmentioning
confidence: 99%